"Not all fish are equal: a Bourdieuan analysis of ableism in a financial services company". Issue 11 (22nd June 2021) - Jammaers, Eline; Zanoni, Patrizia; Williams, Jannine
Abstract: Responding to recent calls to extend our understanding of ableism as a powerful organizing principle of the workplace, this study examines how ableism operates as a form of symbolic violence, constraining the career opportunities of disabled employees in a financial services company. Drawing on Bourdieuan theory, we analyze how the 'rules of the game' structuring the organizational field and the habitus of disabled individuals jointly shape those individuals' ability to accrue economic, social, cultural as well as symbolic capital, as well as up different positions in a particular social space. A Bourdieuan approach centered on social practice allows us to develop a fuller understanding of the mechanisms through which valued forms of capital are unequally distributed within an arbitrary social order that privileges certain competences favoring able-bodied over disabled workers, and of disabled workers' own role within such mechanisms.